Porous Scaffold-Hydrogel Composites Spatially Regulate 3D Cellular Mechanosensing - DiCerbo, Matthew; Benmassaoud, Mohammed Mehdi; Vega, Sebastián L. (Frontiers in Medical Technology, 2022)
Cells encapsulated in 3D hydrogels exhibit differences in cellular mechanosensing based on their ability to remodel their surrounding hydrogel environment. Although cells in tissue interfaces feature a range of mechanosensitive states, it is challenging to recreate this in 3D biomaterials. Human mesenchymal stem cells (MSCs) encapsulated in methacrylated gelatin (GelMe) hydrogels remodel their local hydrogel environment in a time-dependent manner, with a significant increase in cell volume and nuclear Yes-associated protein (YAP) localization between 3 and 5 days in culture. A finite element analysis model of compression showed spatial differences in hydrogel stress of compressed GelMe hydrogels, and MSC-laden GelMe hydrogels were compressed (0–50%) for 3 days to evaluate the role of spatial differences in hydrogel stress on 3D cellular mechanosensing. MSCs in the edge (high stress) were significantly larger, less round, and had increased nuclear YAP in comparison to MSCs in the center (low stress) of 25% compressed GelMe hydrogels. At 50% compression, GelMe hydrogels were under high stress throughout, and this resulted in a consistent increase in MSC volume and nuclear YAP across the entire hydrogel. To recreate heterogeneous mechanical signals present in tissue interfaces, porous polycaprolactone (PCL) scaffolds were perfused with an MSC-laden GelMe hydrogel solution. MSCs in different pore diameter (~280–430 μm) constructs showed an increased range in morphology and nuclear YAP with increasing pore size. Hydrogel stress influences MSC mechanosensing, and porous scaffold-hydrogel composites that expose MSCs to diverse mechanical signals are a unique biomaterial for studying and designing tissue interfaces.